Comparative Dimensional Accuracy of Dovetail and Airfoil EDM Defect on Gas Turbine Blades Using Camera Image and Micrometer - Maulana Yusuf Izzuddin; Sampurno; Muhammad Thaliban Habib Hudzaifah Na’im; Muhammad Rafi Kalevi; Bismaka Adhipramana Pinggala (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2026)
Gas turbine blades experience severe thermo-mechanical loading; therefore, dimensional examination of damage features must be accurate, repeatable, and non-destructive. This study develops and validates a non-contact digital image processing workflow to quantify artificial defects produced by die-sinking electrical discharge machining (EDM) on two blade regions with distinct surface characteristics: a serrated dovetail joint and a smooth airfoil. Six defects were manufactured (three per region) with nominal depths of 0.5, 1.0, and 2.0 mm. Repeatability was assessed using 20 measurements per defect (120 total) to determine accuracy via relative error and precision via standard deviation, followed by non-parametric and variance testing, and validation against a 0.001 mm resolution digital micrometer. Planar dimensions (length and width) achieved 97.5-99.9% accuracy, with overall accuracy above 95% and no significant difference in median accuracy between regions (P = 0.577). Precision was significantly lower on the dovetail (P < 0.001), attributed to serration-driven shadows and specular reflections that degrade edge stability. Micrometer comparisons showed minimal deviation for straight line features, while airfoil measurements captured a more representative two-dimensional projected profile than chord-based contact readings. The results demonstrate a rapid, low-cost, and surface-safe inspection approach, while highlighting optical constraints that must be controlled to ensure consistent metrology on complex turbine geometries.